2021
DOI: 10.3389/fpsyt.2021.712178
|View full text |Cite
|
Sign up to set email alerts
|

FAAH and CNR1 Polymorphisms in the Endocannabinoid System and Alcohol-Related Sleep Quality

Abstract: Sleep disturbances are common among individuals with alcohol use disorder (AUD) and may not resolve completely with short-term abstinence from alcohol, potentially contributing to relapse to drinking. The endocannabinoid system (ECS) is associated with both sleep and alcohol consumption, and genetic variation in the ECS may underlie sleep-related phenotypes among individuals with AUD. In this study, we explored the influence of genetic variants in the ECS (Cannabinoid receptor 1/CNR1: rs806368, rs1049353, rs64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…It was found that subjective sleep disturbances differed significantly among CNR1 rs6454674 genotypes in both subjects with AUDs and the controls, but only among the controls, neuroticism personality scores mediated the relationship between genotype and sleep disturbances. On the other hand, objective sleep measures differed significantly by the CNR1 rs806368 genotype, both at baseline and follow-up, and the FAAH rs324420 genotype for recorded sleep duration among individuals with AUD at follow-up [434].…”
Section: Genetic Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…It was found that subjective sleep disturbances differed significantly among CNR1 rs6454674 genotypes in both subjects with AUDs and the controls, but only among the controls, neuroticism personality scores mediated the relationship between genotype and sleep disturbances. On the other hand, objective sleep measures differed significantly by the CNR1 rs806368 genotype, both at baseline and follow-up, and the FAAH rs324420 genotype for recorded sleep duration among individuals with AUD at follow-up [434].…”
Section: Genetic Studiesmentioning
confidence: 90%
“…In WT mice, LY2828360 blocked morphine-induced reward in a CPP paradigm, whereas morphine-induced reward was absent in CB2r KO mice. LY2828360 partially attenuated naloxone-precipitated opioid withdrawal in morphine-dependent WT mice, whereas this withdrawal was markedly exacerbated in CB2r KO mice [474] Animals Maternally deprived adolescent rats Maternally deprived adolescent rats exhibited ↑ AEA in the NAcc, the Cpu nucleus, and the mesencephalon Maternally deprived adult rats, showed ↑ AEA and 2-AG in the NAcc, and ↑ 2-AG in the CPu nucleus [177,273,275] [193,195,196,230,231,233,269,271,271, 276,375,376,396,397,430,434] [134] [234,271,396] [234] [234,269,270,375,396,430,434,451,460,470] [396]…”
Section: Authorsmentioning
confidence: 99%
“…In a study developed by Bühler and colleagues, authors evaluated the involvement of 10 SNPs of different targets, two of them corresponding to the FAAH gene. The positive rating of alcohol-related pictures was associated with the homozygous CC C38A SNP genotype, indicating that this SNP is a candidate for screening patients with a higher risk of alcoholrelated problems, such as sleep disturbances [44,45]. This correlation appears to be different depending on the ethnic factors.…”
Section: Gene Polymorphisms Of Ecs Componentsmentioning
confidence: 96%
“…AUD research has frequently investigated the endocannabinoid system (ECS) function, a widely distributed neuromodulatory system associated with central nervous system development and synaptic plasticity [14][15][16]. It includes cannabinoid receptors (CB1 and CB2), endogenous cannabinoids, and the endocannabinoid degrading system (FAAH-fatty acid amide hydrolase).…”
Section: Introductionmentioning
confidence: 99%